Assessing for domestic violence - Harway, Michele; Andrews & Clark Explorations, Inc ([Los Angeles, Calif. : Andrews & Clark Explorations ; New York : Distributed by Insight Media], 2004)
Asserts that all mental health professionals, even those who do not specialize in domestic violence, need to be prepared to recognize and work with domestic violence issues presented by their clients. Provides an introduction to violence in marriages and other intimate relationships and explains Lenore Walker's cycle of violence. Offers directions for assessing a mental health client in a first interview
Title from title screen
Host: Michele Harway
Keywords: Family violence -- Psychological aspects